Arquitetura genética do comportamento materno de construção de ninho - Silva, Bruno Sauce (2010)
Genetic architecture of a phenotype represents the total number of genes, independent effects (additivity), the interactions between alleles (dominance and epistasis), and its effects on other phenotypes (pleiotropy). An enormous debate about general types of genetic architectures relates the importance of independent and interactive variation in the adaptive process. Because natural selection reduces additive variation, we expect, of fitness related phenotypes, lesser additive than interactive variation and relatively more genes with moderate effects. Maternal care is a phenotype with enormous importance to fitness. Of the maternal care behaviors, the nest building highlights itself improving pups survival by protection against predators and temperature maintenance. We investigated the genetic architecture of nest building in mice and tested the hypothesis that this behavior has a genetic architecture related to fitness, also verifying possible associations with anxiety and weight. For that, we checked the relation between all phenotypes and tested, using the QTL analysis, the phenotypic association with regions (microsatellites markers) spread about all genome of F2 females at maternal stage from the intercross of inbred strains SM/J and LG/J. We found 23 QTLs which, individually, are associated with phenotypic variation on nest building, weight and anxiety (15 QTLs at the 6 nest building phenotypes). The nest building s individual QTLs have moderate effects (from 4 to 13%), and the numerous epistatic QTLs add to increase this explained variation. There are common regions for nest building with anxiety and weight and, searching for candidate genes, we found genes with effects already described for these phenotypes. Hence, we corroborate our hypothesis of the genetic architecture type related to fitness for nest building behavior, of genes with bigger effects and high interactive variation. The identification of regions associated with maternal care in mice and the knowledge of the related genetic architecture can help in identifying genes for these behaviors in other mammals, and in the comprehension of general patterns in adaptive process and life evolution.